On new realizations of the poincare groups P (1,2) and P(2, 2) - Zhdanov, R. Z.; Lagno, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We classify realizations of the Poincare groups P (1, 2) and P (2, 2) in the class of local Lie groups of transformations and obtain new realizations of the Lie algebras of infinitesimal operators of these groups.